PRAKTIKALITAS MEDIA VIDEO TUTORIAL SEBAGAI SUPLEMEN DIGITAL LEARNING PADA MATA KULIAH PERSAMAAN DIFERENSIAL BIASA - Rifandi, Ronal; Ahmad, Defri; Gusteti, Meria Ultra (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Industrial revolution 4.0 in which digital technology being more integrated in all aspects of human life will demand the new reform of education world. Not only can it affect the curriculum being taught, but it will also lead to the changes of the methods and approaches in conducting the lesson. One of the changes is the use of digital learning. Universitas Negeri Padang has regulation of conducting lesson through e-learning platform proportionally for all courses, including the course of Ordinary Differential Equation. Ordinary Differential Equation is a mandatory course that should be taken by mathematics department?s students. In order to support students to develop their under standing about the concept and its application while using digital learning method, the researchers develop some tutorial video as supplementary media. Therefore, this study aimed to describe the practicality of the tutorial video. This is a descriptive research where the data were collected using closed questionnaire. The respondents were 39 mathematics students of Universitas Negeri Padang who joined Ordinary Differential Equation Course in the semester of January-June 2020. The result indicates that the video tutorials used in the course are in the category of very practice with the score percentage 86,6%.